Predictors of Intention to Travel to Cuba across Three Time Horizons: An Application of the Theory of Planned Behavior. (September 2018) - Jordan, Evan J.; Bynum Boley, B.; Knollenberg, Whitney; Kline, Carol
As the relationship between Cuba and the United States evolves, many Americans are entertaining the idea of travel to Cuba. This study used the Theory of Planned Behavior (TPB) to examine predictors of US residents' intentions to travel to Cuba across three time horizons: 1 year, 5 years, and 10 years. TPB constructs were administered to a cross-sectional panel of US residents. Results varied by time horizon, with US residents' negative attitudes toward Cuba having a positive and significant influence on their intention to visit Cuba within one year. This finding suggests that some US residents match Plog's Allocentric profile of tourists and that the current "rough edges" of Cuba are what attract them to travel in the short rather than long term. Findings from this study provide baseline data that is valuable for Cuban and American tourism organizations, should the US market become more accessible.